Modernisasi Sistem Pendidikan Pondok Pesantren - Muhammad Zamroji (Muróbbî: Jurnal Ilmu Pendidikan, 2017)
Islamic Boarding School is an Islamic institution which has the advantage both from the aspect scientific tradition or transmission side and intensity of Muslims. The swift currents of globalization push present of ideas modernization for the challenges needs of social transformation. However, not a little worrying ideas can affect identity and function of the principal. The modernisation of Boarding Schools involves three aspects; curriculum; learning model; and institutional structures. From the three models, refer to the intent and purpose of which is to maintain the balance of theoretical aspects and scientific aspects (practice), but it also meets stock to the students both temporal and hereafter in all fields, so that the students can have the achievements of science in the science of religion and also general science.